Tingkat Pemahaman Etika Bisnis Islam Pedagang Pasar Kebon Watu Gede - Ulya Minata Rusdiati; Effi Wahyuningsih; Mohammad Abdul Munjid; Mohammed Hafiz Ali Wafa (Yayasan Azhar Amanaa Yogyakarta, 2023)
Islamic Business Ethics is a procedure for studying right or wrong behavior in doing business based on Islamic values. The values or principles that exist in Islam include the principle of unity, the principle of balance or justice, the principle of free will, the principle of honesty and the principle of responsibility. This research was conducted to test how knowledgeable the Kebon Watu Gede Market traders are. There were 31 informants in this study including 26 traders, 1 manager, and 5 buyers of Kebon Watu Gede Market. This type of research is using field research to obtain accurate information regarding existing phenomena. Data collection techniques using observation and interviews. The results showed that the level of understanding of Kebon Watu Gede Market traders had reached the highest stage (extrapolation), and Kebon Watu Gede Market traders had applied the principles of Islamic business ethics.